The potential of artificial live rock as subtrate for coral spat and epibenthic organisms - Yusof, Muhammad Hamizan; Saad, Shahbudin; Nordin, Noor Faizul Hadry; Y, Mahfuzah; R, Rafindde; Khodzori, Mohd Fikri Akmal; R, Mohd Husaini (Universiti Teknologi Malaysia, 2015)
Over-exploitation on natural live rock promotes the degradation of ocean ecosystem. This concern has been raised since harvesting may reduce the density of marine ornamentals and degrade marine habitat quality. This study aims to develop artificial live rocks (ALR) that potentially to be used as one of the alternatives to reduce the overharvesting activity toward natural live rocks. The study was conducted at Bidong Island, Terengganu started from April to October 2014. There were 2 types of ALR used in this study; rough and smooth surfaces. A total of 64 pieces of ALR were deployed in April 2014 and retrieved in June, August and October 2014 respectively. Identification in terms of coral spat species and macrobenthic organisms was done after the each retrieval. Coral spat was identified based on the morphology of their columella, septa and corallite wall by using Dinolight Digital Camera. Four species of coral juveniles (Pocillopora damicornis, Stylophora pistillata, Seriatopora hystrix and Acropora millepora) were found attached on ALR surfaces. Whereby, there were 11 phyla of epibenthic organisms were found to attach on ALR which dominated by turf algae and red algae. Percentage coverage of epibenthic calculated using Coral Point Count with Excel extension (CPCe) shown ALR was dominated by turf algae after 2 months (69%) and 4 months (20%) of deployment respectively. Afterward, Red algae (31%) dominated after 6 months of deployment. There was significant difference between coral species and the surfaces (p<0.05). However, no significant difference between types of surfaces with sessile macrobenthic organisms (p>0.05). This finding showed that ALR has a potential to be upgraded as artificial reef towards marine habitat restoration.